(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The damage from weeds in the cultivation of agricultural crops is ubiquitous and they adversely affect the yields of agricultural production. The soil conditions of the places where the crops are grown deteriorate. Contribute to the development of diseases and the enemies on them. Apart from this, it is difficult to carry out mechanized processing and harvesting activities. Weeds also worsen the very quality of the harvested produce. That is why the availability of a recognition system to the agricultural robot is essential to reduce the adverse influence. It is part of a system of control and destruction. In this weed recognition system, an essential element is a robotic arm to enable a camera to perform video surveillance.The aim of this paper is to modelling only the mechanical anchorage system for weed recognition elements that it does not interfere with the other elements with which it interacts. To be as effective as possible, this system must be as close as possible to the plants and at the same time close to the weed eradication system in agricultural robot.A three-dimensional model of the weed recognition mechanical parts from system is discussed in the paper. It is designed in a 3D Experience environment, taking into account the parameters necessary for the movement of the system. Strength sizing of the structure and working simulations of the model were made.